Survival after Liver Transplantation for Hepatitis C Is Unchanged over Two Decades in Canada. (2008) - Watt, Kymberly DS; Burak, Kelly W; Deschênes, Marc; Lilly, Les; Marleau, Denis; Marotta, Paul; Mason, Andrew; Peltekian, Kevork M; Renner, Eberhard; Yoshida, Eric M; for the Canadian Transplant Hepatology Outcomes Research Network,
Abstract : Allograft failure secondary to recurrence of hepatitis C virus (HCV) infection is the most common cause of death and retransplantation among recipients with HCV infection. It has been suggested that patients transplanted for HCV have had worse outcomes in more recent years than in previous years (the 'era effect'). A Canadian transplantation registry database was analyzed to determine the outcomes of patients transplanted over the years for HCV. The results of the present analysis of 1002 patients show that the 'era effect' was not seen in liver transplantation recipients with HCV in Canada, because no survival difference was noted based on the year of transplantation. All groups had overall two-year and five-year survival rates of 76% to 83% and 69% to 72%, respectively. The present study's national results prove continued benefit to transplantation of HCV patients.